If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -1y = 12 + 0y Anything times zero is zero. -8 + -1y = 12 + 0y Combine like terms: 12 + 0 = 12 -8 + -1y = 12 Solving -8 + -1y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1y = 12 + 8 Combine like terms: -8 + 8 = 0 0 + -1y = 12 + 8 -1y = 12 + 8 Combine like terms: 12 + 8 = 20 -1y = 20 Divide each side by '-1'. y = -20 Simplifying y = -20
| 4x+3(x-2)=7(x-2)+8 | | 9(-8)-13=-31 | | mxn=2-d | | m*n=2-d | | 4(x+2)+6=2x+2x+14 | | 5a^3(5a^2+2)= | | 3x+7-x=2x+21 | | 3x(4x+3-5)=58 | | 10/x=3/2x+34 | | 6s-3(5s+2)=4-5s | | y=0.5x^2-3x+4 | | 5a^3(5a^2+2)=25a^5+10a^3 | | (6-x)(6+x)-(x-11)x=18 | | x+(-1/2)=4 | | x=4.2+-0.5y | | 10x+5y=42 | | 5y=3x+2forx | | 4.00/5.00x=20 | | x^2+17.4*x-17.4=0 | | (x+3/2)+(3/4)=(3x/2)-1 | | x^2/(2-2x)-8.7=0 | | x^2/(2-2x)=8.7 | | (6x/8)+(4x/2)-5=(3x/4) | | 187+15/100 | | 3x^2-3y=0 | | (5/12)-(1/3x)=(2/3x)-(7/6) | | (3x/2)+(1/2)=(4x/5)+(3/5) | | 3xy-6x=0 | | (4x/6)+(x/5)=(2/3)-(x/5) | | 41/2+11/6=4 | | 183-7x=29x+19 | | 2x+132=7x-13 |